Integrated Analysis of Large-Scale Omics Data Revealed Relationship Between Tissue Specificity and Evolutionary Dynamics of Small RNAs in Maize (Zea mays) - Xu, Yu; Zhang, Ting; Li, Yuchen; Miao, Zhenyan (Frontiers in Genetics, 2020)
The evolutionary dynamics and tissue specificity of protein-coding genes are well documented in plants. However, the evolutionary consequences of small RNAs (sRNAs) on tissue-specific functions remain poorly understood. Here, we performed integrated analysis of 195 deeply sequenced sRNA libraries of maize B73, representing more than 10 tissues, and identified a comprehensive list of 419 maize microRNA (miRNA) genes, 271 of which were newly discovered in this study. We further characterized the evolutionary dynamics and tissue specificity of miRNA genes and corresponding miRNA isoforms (isomiRs). Our analysis revealed that tissue specificity of isomiR events tends to be associated with miRNA gene abundance and suggested that the frequencies of isomiR types are affected by the local genomic regions. Moreover, genome duplication (GD) events have dramatic effect on evolutionary dynamics of maize miRNA genes, and the abundance divergence for tissue-specific miRNA genes is associated with GD events. Further study indicated that duplicate miRNA genes with tissue-specific expression patterns, such as miR2275a, a phased siRNA (phasiRNA) trigger, contribute to phenotypic traits in maize. Additionally, our study revealed the expression preference of 21- and 24-nt phasiRNAs in relation to tissue specificity. This large-scale sRNAomic study depicted evolutionary implications of tissue-specific maize sRNAs, which coordinate genome duplication, isomiR modification, phenotypic traits and phasiRNAs differentiation.